AN ALGORITHM TO MINIMIZE SINGLE VARIABLE POLYNOMIAL, FUNCTIONS FROM ANY STARTING POINT WITH QUADRATIC CONVERGENCE - Thorne, James; Greening, Doran; Woolsey, Robert E.D. (The South African Journal of Industrial Engineering, 2012)
Search methods often display non-convergence or excessive convergence time on certain classes of nonlinear functions arising in engineering design. The authors will define a new geometric -programming based search method for single variable polynomials that displays quadratic convergence from any starting point Comparison over a group of test problems is made with a version of Newton's method